FORMULATION AND CHARACTERIZATION OF NANOEMULGEL OF SAPPAN WOOD EXTRACT (Caesalpinia sappan L.) WITH CMC-Na VARIATION AS GELLING AGENT - Fikria Marfuatin Nur; Joice Halima Moto; Novamei Indriani (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Sappan wood (Caesalpinia sappan L.) contains brazilin, a major bioactive compound with antioxidant, anti-inflammatory, and antibacterial activities. However, its poor water solubility and low chemical stability limit its therapeutic potential, requiring an improved delivery system such as nanoemulgel to enhance penetration, stability, and topical efficacy. Previous research formulated nanoemulgel using 3–5% CMC-Na but did not include particle size analysis or flavonoid content determination, leaving gaps in stability and active compound retention. This study addresses these limitations by developing nanoemulgel with 2%, 3%, and 4% CMC-Na. The extract was obtained by maceration using 96% ethanol, followed by TLC identification and flavonoid quantification via UV–Vis spectrophotometry. Formulations were evaluated for organoleptic properties, pH, viscosity, spreadability, adhesiveness, homogeneity, particle size, physical stability, and final flavonoid content. The 3% CMC-Na formulation demonstrated the most balanced characteristics, nano-sized particles, and good overall stability.